Ethnic Coalitions of Convenience and Commitment: Political Parties and Party Systems in Kenya - Sebastian Elischer (German Institute of Global and Area Studies (GIGA), 2008)
This paper analyzes the role of ethnicity in shaping the character of Kenya's political parties and its party system since 1992. Drawing on a constructivist conception of ethnicity, it uses a framework of comparison derived from Donald Horowitz and distinguishes between three party types: the mono-ethnic party, the multi-ethnic alliance type and the multi-ethnic integrative type. It shows that although Kenyan parties have increasingly incorporated diverse communities, they have consistently failed to bridge the country's dominant ethnic cleavages. Consequently, all of Kenya's significant parties represent ethnic coalitions of convenience and commitment and, thus, ethnic parties. The paper further states that the country's post-2007 political environment is a by-product of the omnipresence of this party type. – – Afrikanische Parteien wurden in der Literatur nur sehr vereinzelt systematisch untersucht. Allerdings wird generell Ethnizität eine große Bedeutung bei der Klassifizierung afrikanischer Parteien zugemessen. Die vorliegende Analyse bestätigt dies für Kenia. Auf der Grundlage von Donald Horowitz-Theorie über politischen Wettbewerb in multiethnischen Gesellschaften werden in der Untersuchung des Einflusses von Ethnizität auf politische Parteien drei Parteitypen unterschieden: die monoethnische Partei, die multiethnische Allianz und die multiethnische integrative Partei. Die Ergebnisse zeigen, dass seit 1992 alle politisch signifikanten Parteien kurzlebige ethnische Koalitionen darstellen. Diese haben seit Einführung des Mehrparteiensystems Konfliktlinien zwischen ethnischen Gruppen verstärkt. Gewaltsame ethnische Konflikte, wie sie nach den Wahlen im Dezember 2007 zu beobachten waren, sind eine Folgeerscheinung dieser Koalitionen.
Keywords: 300; social cleavages; ethnicity; political party identification; Kenya